Use of beeswax as an alternative binder in the development of composite electrodes: an approach for determination of hydrogen peroxide in honey samples - de Oliveira, Paulo Roberto; Kalinke, Cristiane; Bonacin, Juliano Alves; Marcolino-Junior, Luiz Humberto; Bergamini, Márcio Fernando; Malaspina, Osmar [UNESP]; Nocelli, Roberta Cornélio Ferreira; Janegitz, Bruno Campos (Elsevier, 2021)
The present paper describes a new way to construct composite electrodes by using beeswax as an alternative binder and graphite powder as the conductive phase. Beeswax can be an attractive binder since it is a biodegradable and renewable material. Also, it attributes to the composite material a good rigidity after dry at room temperature. The monitoring of hydrogen peroxide (H2O2) in honey is extremely important due to its antibacterial properties, which are vital for the maintenance of the hive. The determination of H2O2 by electrochemical techniques is widely noted in the literature, mainly using redox mediators or catalysts, such as Prussian blue (PB). Therefore, the proposed composite electrode was prepared with beeswax and graphite in n-hexane, and the PB was electrochemically synthesized by cyclic voltammetry. The constructed electrode showed a low resistance of electronic transfer (60 Ω), high electroactive surface area, and high electronic transference constant (1.73×10−3 cm s−1) when compared with other composite electrodes. The presence of PB on composite electrode allowed the amperometric determination of H2O2 with good linearity (R2 = 0.997) at a concentration range of 1.0−180 µmol L−1 H2O2, showing a sensitivity of 0.184 µAL µmol−1. Consequently, it was possible to determine H2O2 accurately at three concentration levels in wild honey samples (RSD = 98.5−102%), suggesting the use of this alternative method for the quality control analysis of honey.
Keywords: Beeswax; Composite Electrode; Honeybee quality control; Hydrogen peroxide; Prussian blue